열왕기하 23장 14절의 신명기적 편집사 연구 - 이은우(LEE Eun Woo) (Changsin nondan, 2021)
이 연구의 목적은 열왕기하 23장 14절에 나타나는 다양한 표현에 대한 통시 적 분석을 통해 이 구절의 편집사를 추적하는 것이다. 이 구절은 요시야 왕이 석상 들을 깨드리고 아세라 목상을 찍고 사람의 해골로 그곳에 채웠다는 전형적인 신명기적인 개혁의 내용을 포함한 독특한 본문으로 오랫동안 학자들의 관심을 받았다. 일부 학자는 이 구절을 요시야 시대의 신명기적 편집 본문으로, 일부 학자는 이 구절을 바빌론 포로기의 신명기 사가의 본문으로 구분한다. 일부는 이 구절의 전반절과 후반절의 시대를 다르게 보기도 한다. 필자는 이 구절에 나타나는 ‘석상들’(twbcm)과 ‘아세라 목상’(~yrva)과 ‘사람의 해골’(~da twmc[)이라는 표현과 여기에 결합한 다양한 동사, rbv와 trk과 alm와 이 동사들의 앞에 나타나는 접속사 ‘와우’(w)와의 관계 등에 관한 입체적인 연구를 통해 이 구절의 편집사를 추적한다. 이 연구를 통해 필자는 이 구절의 기본층은 14ab절의 ‘아세라 목상을 찍었다’(~yrvah-ta trkyw)는 표현으로 요시야가 앗수르의 종교적 영향을 제거하기 위한 개혁을 단행했다는 사실을 강조하는 요시야 시대의 신명기적 편집층이라는 사실을 밝혀낸다. 이 구절에 첨가된 첫 번째 편집층은 14b절의 ‘그가 사람의 해골로 그것들이 있던 자리를 채웠다’(~da twmc[ ~mwqm-ta almyw)는 표현으로 열왕기하 23장 16절의 whamjyw xbzmh-l[ Îtwmc[Ð @rfyw라는 기본 표현을 참고해서 신명기의 바빌론 포로기의 편집층에 나타나는 alm 동사를 활용해 열왕기하 23장 15-20절의 사람의 해골로 벧엘의 산당을 부정하게 한 북이스라엘에서 행해진 요시야의 개혁이 남유다의 솔로몬의 산당과 관련된 우상 숭배 장소에서도 진행되었다는 것을 강조하는 바빌론 포로기의 신명기적 편집층이다. 이 구절에 첨가된 마지막 편집층은 14aa절의 ‘석상들을 깨뜨렸다’(twbcmh-ta rbvw)라는 어구로 rbv 동사와 hbcm가 결합한 이 형태는 신명기 7장 5절과 12장 3절에도 나타나는 전형적인 신명기적 표현으로 접속사 w와 rbv 동사가 결합한 형태는 열왕기하 23장에서 문맥의 흐름을 단절시키며 나타나는 포로 이후에 wayyiqṭol을 대신하던 weqaṭal 형태 (4bb, 5a, 5b, 8b, 10, 12bb)이다. 포로 이후의 이 편집자는 요시야의 개혁이 솔로몬 산당에 있던 돌기둥 모양의 우상을 개혁하는 데까지 이르렀다는 것을 강조한다. 이 연구를 통해 요시야의 제의 정화 개혁 본문인 열왕기하 23장 14절이 요시야 시대에 형성되었을 뿐 아니라 바빌론 포로기와 포로 귀환 이후까지 신앙 공동체의 위기 때마다 이를 극복하기 위해 계속해서 편집 확장되었음을 확인하게 된다. The purpose of this study is to pursue the redactional history of 2 Kings 23:14 through diachronic analysis on the expressions in this verse. This verse has long attracted the attention of scholars as a unique text containing the typical Deuteronomic reform report that King Josiah broke stone pillars, stamped Asherim and filled them with human bones. Some scholars classify this verse as a Deuteronomic editorial text from Josiah's time, and some as a text from the Deuteronomic editorial text of the Babylonian exile. Some view the times of the first and second half of this verse differently. This writer traces the redactional history of this verse through a three-dimensional analysis of the relationship among the expressions ‘stone pillars’ (twbcm), ‘Asherim’ (~yrva) and ‘human bones’ (~da twmc[) appearing in this verse, and various verbs combined here (rbv, trk, alm), and the conjunction ‘wow’ (w) that appears in front of the verbs. Through this study, the writer reveals that the basic layer of this verse is the expression ‘he cut down the Asherim’ in verse 14ab, , , , the Deuteronomic redactional layer of Josiah’s period stressing the fact that Josiah executed reform to eliminate the religious influence from the Assyrian empire. The first editorial layer added to this verse is the expression ‘he filled their places with human bones' in verse 14b(~da twmc[ ~mwqm-ta almyw) referencing the basic expression related with human bones whamjyw xbzmh-l[ Îtwmc[Ð @rfyw in 2 Kings 23:16 and utilizing the verb alm in Deuteronomy which mainly appears in the redactional layer of Babylonian exile. This phrase signifies the Deuteronomic redactional layer of Babylonian exile which emphasizes Josiah’s reform desanctifying idol worshipping places in Judah. The last redactional layer added to this verse is the phrase ‘he broke the stone pillars to pieces’ (twbcmh-ta rbvw) in verse 14aa. This form, which combines the verb rbv and hbcm, is a typical Deuteronomic expression that also appears in Deuteronomy 7:5 and 12:3. In 2 Kings 23, the combined form of the conjunction w and the verb rbv is the weqaṭal form (4bb, 5a, 5b, 8b, 10, 12bb) that replaced wayyiqṭol after the Babylonian captivity, which appeared in 2 Kings 23, breaking the flow of context. KCI Citation Count: 1